Stories of Challenge (assessment of political commitment and policy traction to address the double burden of malnutrition) in selected countries - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Study will be conducted in 3-4 countries (tbc); global selected as a placeholder for now